2006
DOI: 10.1007/s10546-006-9087-z
|View full text |Cite
|
Sign up to set email alerts
|

Organised Motion in a Tall Spruce Canopy: Temporal Scales, Structure Spacing and Terrain Effects

Abstract: This study investigates the organised motion near the canopy-atmosphere interface of a moderately dense spruce forest in heterogeneous, complex terrain. Wind direction is used to assess differences in topography and surface properties. Observations were obtained at several heights above and within the canopy using sonic anemometers and fast-response gas analysers over the course of several weeks. Analysed variables include the three-dimensional wind vector, the sonic temperature, and the concentration of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 46 publications
(71 reference statements)
6
59
0
Order By: Relevance
“…Figure 1 (FrC) and force convection (FoC)] and near-neutral (NN) conditions and are less dependent under stable conditions. The reason for the insignificant phenology influence on the exchange coefficients under stable stratification could be that under stable conditions the decoupling between the canopy and the atmosphere is independent from canopy density/sparsity (Thomas and Foken 2007). Therefore, we focus our analysis on the stability range from FrC to NN.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 (FrC) and force convection (FoC)] and near-neutral (NN) conditions and are less dependent under stable conditions. The reason for the insignificant phenology influence on the exchange coefficients under stable stratification could be that under stable conditions the decoupling between the canopy and the atmosphere is independent from canopy density/sparsity (Thomas and Foken 2007). Therefore, we focus our analysis on the stability range from FrC to NN.…”
Section: Resultsmentioning
confidence: 99%
“…Because the velocimeter was acquiring data at 8 Hz, to directly compare its wavelet spectrum with that of w9 both of the datasets were block averaged down to 2 Hz. This is a feasible option because the coherent structures in w9 are expected to be below this frequency and the loss of high-frequency detached eddies should not significantly affect the results (Thomas andFoken 2005, 2007). In wavelet analysis the maximum allowable time scale must be the next power of 2 below half the length of the time series.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6). The computation of the CWT, XWT, WTC, and global wavelet variance was carried out in Matlab version 7.4a following the methods outlined by Torrence and Compo (1998), Thomas and Foken (2005), and Grinsted et al (2004) using scripts written by Torrence and Compo (1998; available online at http://paos.colorado.edu/research/ wavelets/) and Grinsted et al (2004; available online at http://www.pol.ac.uk/home/research/waveletcoherence). Determining the strength of any interference from water pressure fluctuations ( p9) on the measurement of w9 required that the individual wave forms, ranging from the 2-to 32-s scale for both time series, be summed and averaged (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, numerous studies have reported geometrical shapes of coherent structures over a variety of surfaces such as land (e.g., Barthlott et al, 2007), ice (e.g., Lykossov and Wamser, 1995), vegetation (e.g., Serafimovich et al, 2011), and water (e.g., Boppe et al, 1999). Ramp-like coherent structures under unstable conditions have been attributed mainly to surface-layer plumes or mixed-layer thermals (e.g., Kaimal and Businger, 1970) but also superposition of shear driven and thermal structures has been reported (Thomas and Foken, 2006). Coherent structures were also detected in stable flows (Kikuchi and Chiba, 1985), and they might appear without the presence of a boundary (Belušić and Mahrt, 2012).…”
Section: Introductionmentioning
confidence: 99%